1997
DOI: 10.1021/ma9616468
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics in Solutions of Associating Statistical Copolymers

Abstract: The association of styrene−methyl methacrylate statistical copolymers in the selective solvent acetone (a thermodynamically good solvent for poly(methyl methacrylate and bad for polystyrene) was examined by static and dynamic light scattering methods. In dilute solutions, the dynamics was dominated by a single fast mode, whereas in semidilute solutions two modes were generally seen, with fast and slow mean relaxation times. The fast dynamic mode was related to the cooperative diffusion mode. The slow mode was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…The data for the LC gels qualitatively resemble those observed from previous light-scattering studies of associating polymers, [23][24][25][26][27][28][29] with the appearance of slow relaxation modes above a critical concentration and highly stretched intensityautocorrelation functions with a strong q-dependence. However, in the present study, the scattered light arises primarily from fluctuations in the orientation of the nematic director, not density fluctuations as in the previous lightscattering studies of gelled systems [23][24][25][26][27][28][29] .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The data for the LC gels qualitatively resemble those observed from previous light-scattering studies of associating polymers, [23][24][25][26][27][28][29] with the appearance of slow relaxation modes above a critical concentration and highly stretched intensityautocorrelation functions with a strong q-dependence. However, in the present study, the scattered light arises primarily from fluctuations in the orientation of the nematic director, not density fluctuations as in the previous lightscattering studies of gelled systems [23][24][25][26][27][28][29] .…”
Section: Discussionsupporting
confidence: 80%
“…However, in the present study, the scattered light arises primarily from fluctuations in the orientation of the nematic director, not density fluctuations as in the previous lightscattering studies of gelled systems [23][24][25][26][27][28][29] . Therefore, structural changes such as micellar diffusion or concentration fluctuations in the polymer network are revealed indirectly by their effect on the nematic-director dynamics.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Nemoto et al [29] found that the line-width of slow relaxation caused by the associated large cluster was independent of q. However, Koňák et al [21] found that the line-width of slow relaxation originating from the associated large cluster could be scaled to q a , a varying from 2.0 to 5.0 with varying the concentration. The slow relaxation mode originating from the associated cluster was found in potato amylopectin solution when C/C* w 2.5.…”
Section: Effect Of Association On the Dynamics Of Amylopectin In Semimentioning
confidence: 99%
“…Dynamic light scattering measurements 13) were reported for the system acetone/poly[styrene-ran-(methyl methacrylate)], where acetone corresponds to the segments of homopolymer A and interacts favorably with the methyl methacrylate units of the copolymer (analogue of the A segments of the present model copolymer A-ran-B) whereas it constitutes a precipitant for the styrene units (analogue of the B segments). The authors conclude that a slow mode they observe in semidilute solutions is due to the dynamics of polydispersed clusters formed by random association of copolymers.…”
Section: Shear Effectsmentioning
confidence: 99%